Lovastatin-mediated changes in human tendon cells - Kuzma-Kuzniarska, M; Cornell, H; Moneke, M; Carr, A; Hulley, P (Wiley, 2015)
Statins are among the most widely prescribed drugs worldwide. Numerous studies have shown their beneficial effects in prevention of cardiovascular disease through cholesterol-lowering and anti-atherosclerotic properties. Although some statin patients may experience muscle-related symptoms, severe side effects of statin therapy are rare, primarily due to extensive first-pass metabolism in the liver. Skeletal muscles appear to be the main site of side effects; however, recently some statin-related adverse effects have been described in tendon. The mechanism behind these side effects remains unknown. This is the first study that explores tendon-specific effects of statins in human primary tenocytes. The cells were cultured with different concentrations of lovastatin for up to 1 week. No changes in cell viability or morphology were observed in tenocytes incubated with therapeutic doses. Short-term exposure to lovastatin concentrations outside the therapeutic range had no effect on tenocyte viability; however, cell migration was reduced. Simvastatin and atorvastatin, two other drug family members, also reduced the migratory properties of the cells. Prolonged exposure to high concentrations of lovastatin induced changes in cytoskeleton leading to cell rounding and decreased levels of mRNA for matrix proteins, but increased BMP-2 expression. Gap junctional communication was impaired but due to cell shape change and separation rather than direct gap junction inhibition. These effects were accompanied by inhibition of prenylation of Rap1a small GTPase. Collectively, we showed that statins in a dose-dependent manner decrease migration of human tendon cells, alter their expression profile and impair the functional network, but do not inhibit gap junction function.